2020
DOI: 10.1038/s41419-020-2653-3
|View full text |Cite|
|
Sign up to set email alerts
|

Intestinal vitamin D receptor knockout protects from oxazolone-induced colitis

Abstract: Crohn's disease (CD) and ulcerative colitis (UC) actually had different pathological mechanisms, as the former was mainly induced by Th1 and Th17 response and the latter by Th2 response. Our previous study found that oxazoloneinduced Th2-mediated colitis could not be attenuated by vitamin D supplementation. This study investigated the influence of intestinal vitamin D receptor (VDR) knockout on oxazolone-induced colitis and explored the possible immunological mechanism. Intestinal VDR knockout mice had milder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…To date, the exact mechanism by which epithelial permeability changes has not been understood. Multiple inflammatory cytokines (such as TNF-a, IL-6, and IL-1β) secreted in the intestinal tract of UC patients may be the main cause of TJ destruction [17]. TJs play an important role in maintaining the integrity of the intestinal mucosal barrier, which is one of the strategies for the treatment of UC [18].…”
Section: Discussionmentioning
confidence: 99%
“…To date, the exact mechanism by which epithelial permeability changes has not been understood. Multiple inflammatory cytokines (such as TNF-a, IL-6, and IL-1β) secreted in the intestinal tract of UC patients may be the main cause of TJ destruction [17]. TJs play an important role in maintaining the integrity of the intestinal mucosal barrier, which is one of the strategies for the treatment of UC [18].…”
Section: Discussionmentioning
confidence: 99%
“…DSS-induced colitis is broadly considered to be a ulcerative colitis–like model, and ulcerative colitis is considered a Th2-immune response (Gonzalez Acera et al 2021). However, the immune response in DSS-induced mice remains controversial (Chassaing et al 2014; Shi et al 2020), emphasizing the necessity to further understand the pathogenic roles of Th1 and Th2 responses in colitis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used NH 3 at a concentration of 25 ± 3 ppm to replicate the environmental stress and observed induction of both IL-1β and IL-10 as well as hemorrhage in the lung tissues. IL-1β and IL-10 are significant cytokines involved in regulating inflammatory response ( Li et al, 2016 ; Zhou et al, 2019 ; Shi et al, 2020 ). The results revealed that critical concentrations of NH 3 induced lung inflammation in broilers.…”
Section: Discussionmentioning
confidence: 99%